Drug sensitivity and genome-wide analysis of two strains of Mycoplasma gallisepticum with different biofilm intensity - Ma, Xiaoyan; Wang, Li; Yang, Fei; Li, Jidong; Guo, Lei; Guo, Yanan; He, Shenghu (Frontiers in Microbiology, 2023)
Mycoplasma gallisepticum (MG) is one of the major causative agents of chronic respiratory diseases in poultry. The biofilms of MG are highly correlated to its chronic infection. However data on genes involved in biofilm formation ability are still scarse. MG strains with distinct biofilm intensity were screened by crystal violet staining morphotyped and characterized for the drug sensitivity. Two MG strains NX-01 and NX-02 showed contrasted ability to biofilm formation. The biofilm formation ability of NX-01 strain was significantly higher than that of NX-02 strain (P < 0.01). The drug sensitivity test showed that the stronger the ability of MG stain to form biofilms, the weaker its sensitivity to 17 antibiotic drugs. Moreover, putative key genes related to biofilm formation were screened by genome-wide analysis. A total of 13 genes and proteins related to biofilm formation, including ManB, oppA, oppD, PDH, eno, RelA, msbA, deoA, gapA, rpoS, Adhesin P1 precursor, S-adenosine methionine synthetase and methionyl tRNA synthetase were identified. There were five major discrepancies between the two isolated MG strains and the five NCBI-published MG strains. These findings provide potential tagets for inhibiting the formation of biofilm of MG, and lay a foundation for treating chronic infection.